Enjoying Bakpia by exploring the Spirit of Tut Wuri Handayani - Pramudito, Aditya; Huda, Dimas Rizky; Fitriana, Regita Nova; Permatasari, Sekar Putri; Sebri, Muhammad; Maulida, Alfiatul (IJCS: International Journal of Community Service, 2024)
The main objective of this program is to provide training and guidance in the social and environmental fields that focus primarily on the development of MSMEs. Community service activities carried out by students and lecturers of the Management Study Program, Sarjanawiyata Tamansiswa University on October 11, 2024 at Bakpia Zahrae 215 have the theme "Enjoy Bakpia by Exploring the Spirit of Tut Wuri Handayani". Bakpia Zahrae 215, which was established in 2017, faces challenges in human resource management due to the absence of a Standard Operating Procedure (SOP). This study proposes the application of the "Tut Wuri Handayani" principle to build a good work culture and improve employee discipline. With this approach, it is hoped that employees can be directed and motivated, and can implement simple SOPs to increase productivity and product quality. The process of preparing SOPs takes time and patience, and it is important for owners to involve consultants or training institutions to create an optimal work environment. The results of this study are expected to support the sustainability of the Bakpia Zahrae 215 business and increase employees' sense of responsibility for their work.